2007
DOI: 10.1007/s00209-006-0076-1
|View full text |Cite
|
Sign up to set email alerts
|

Presenting affine q-Schur algebras

Abstract: Abstract. We obtain a presentation of certain affine q-Schur algebras in terms of generators and relations. The presentation is obtained by adding more relations to the usual presentation of the quantized enveloping algebra of type affine gl n . Our results extend and rely on the corresponding result for the q-Schur algebra of the symmetric group, which were proved by the first author and Giaquinto.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(67 citation statements)
references
References 23 publications
2
65
0
Order By: Relevance
“…Another consequence of the existence of the quotient map (6.3.4) is a simple description of S Q (n; r, s) by generators and relations, generalizing the presentation of S Q (n, d) obtained in [DG2]. We recall the elements ε 1 , .…”
Section: Generators and Relationsmentioning
confidence: 97%
See 3 more Smart Citations
“…Another consequence of the existence of the quotient map (6.3.4) is a simple description of S Q (n; r, s) by generators and relations, generalizing the presentation of S Q (n, d) obtained in [DG2]. We recall the elements ε 1 , .…”
Section: Generators and Relationsmentioning
confidence: 97%
“…In light of results of [DG2] it is now clear how one might define a natural candidate for the rational q-Schur algebra. It is the Q(v)-algebra (v an indeterminate) given by generators E i , F i (1 i n − 1) and…”
Section: Proposition 72 Assume That N 2 and Setmentioning
confidence: 99%
See 2 more Smart Citations
“…In [1] (see also [5]) it is shown that the q-Schur algebra is a homomorphic image θ(U q ) of a modified quantized enveloping algebraU q . ThisU q can be obtained from the quantized enveloping algebra U q of the general linear group, using the triangular decomposition U q = U − U 0 U + of U q , replacing U 0 by a direct sum of infinitely many one-dimensional algebras, generated by idempotents 1 λ , one for each weight λ.…”
Section: Introductionmentioning
confidence: 99%